Delimitação de corredor ecológico na Serra da Piedade, Minas Gerais, utilizando geotecnologias - Araujo, Cassio Fernandes de (2022)
The inclusion of corridors is a strategy to mitigate the effects of habitat fragmentation on biodiversity. Corridors enable connectivity and gene flow between plant and animal populations across isolated patches of habitat and within fragmented landscapes. Over the last two decades, the use of models for the design and location of ecological corridors has been consolidated, supported by geotechnologies. One of the most widespread models is the Least-Cost Path Analysis (LCP), which results in the best route for locating corridors. The main objective of this work is to propose the best methodology for the implementation of an ecological corridor between two priority areas for biodiversity conservation in the Serra da Piedade region, using QGIS. With this, we intend to propose a methodology to mitigate the effects of forest fragmentation in Serra da Piedade, State of Minas Gerais. The specific objectives were: (i) to process the ALOS PALSAR Digital Elevation Model to generate the slope map; (ii) generate the matrix images of land use and land cover costs, Permanent Preservation Areas, slope and fragments of native vegetation; and (iii) measure the total cost surface, obtain the routes of corridors and choose the best way to compose the final ecological corridor. Thus, the corridor was delimited using the factors: land use and cover, Permanent Preservation Areas, fragments of native vegetation and slope. For each cost matrix image, its respective statistical weight was calculated using the multicriteria decision method – Analytic Hierarchy Process (AHP). With the development of this work, it was determined that the class “Native Forest” is the predominant class in the study area. The percentage of the area destined to permanent preservation in the conflict with the established by the current legislation is 26,58%. In the final corridor proposed by the model, there is a predominance of the “Native Forest” class, accounting for 72,7% of corridor area. The interconnection between the two priority areas with the chosen corridor respected a width equal to 10% of its lenght, in accordance with the guidelines contained in Conama no 09/96. Thus, the chosen Ecological Corridor is 15.768,920 meters long and 1.576,892 meters wide. It is concluded that the LCP model associated with the result generated by multi-criteria decision method (AHP) and combined with QGIS is an important tool for planning, design and implementation of ecological corridors because it considers key factors in the decision-making process.